Surgical approaches to the facial skeleton - Ellis, Edward, DDS; Zide, Michael F. (Wolters Kluwer, 2018)
"This text/atlas is a step-by-step guide to the surgical approaches used to expose the facial skeleton. The authors describe in detail the key anatomic structures and the technical aspects of each approach, so that the surgeon can safely gain access to the region of the craniofacial skeleton requiring surgery"--Provided by publisher